Prediction of response to remission induction therapy by gene expression profiling of peripheral blood in Japanese patients with microscopic polyangiitis. Issue 1 (December 2017) - Ishizu, Akihiro; Tomaru, Utano; Masuda, Sakiko; Sada, Ken-ei; Amano, Koichi; Harigai, Masayoshi; Kawaguchi, Yasushi; Arimura, Yoshihiro; Yamagata, Kunihiro; Ozaki, Shoichi; Dobashi, Hiroaki; Homma, Sakae; et al.
Abstract Background Microscopic polyangiitis (MPA), which is classified as an anti-neutrophil cytoplasmic antibody (ANCA)-associated small vessel vasculitis, is one of the most frequent primary vasculitides in Japan. We earlier nominated 16 genes (IRF7, IFIT1, IFIT5, OASL, CLC, GBP-1, PSMB9, HERC5, CCR1, CD36, MS4A4A, BIRC4BP, PLSCR1, DEFA1/DEFA3, DEFA4, andCOL9A2 ) as predictors of response to remission induction therapy against MPA. The aim of this study is to determine the accuracy of prediction using these 16 predictors. Methods Thirty-nine MPA patients were selected randomly and retrospectively from the Japanese nationwide RemIT-JAV-RPGN cohort and enrolled in this study. Remission induction therapy was conducted according to the Guidelines of Treatment for ANCA-Associated Vasculitis published by the Ministry of Health, Labour, and Welfare of Japan. Response to remission induction therapy was predicted by profiling the altered expressions of the 16 predictors between the period before and 1 week after the beginning of treatment. Remission is defined as the absence of clinical manifestations of active vasculitis (Birmingham Vasculitis Activity Score 2003: 0 or 1 point). Persistent remission for 18 months is regarded as a "good response, " whereas no remission or relapse after remission is regarded as a "poor response." Results "Poor" and "good" responses were predicted in 7 and 32 patients, respectively. Five out of 7 patients with "poor" prediction and 1 out of 32 patients with "good" prediction experienced relapse after remission. One out of 7 patients with "poor" prediction was not conducted to remission. Accordingly, the sensitivity and specificity to predict poor response was 85.7% (6/7) and 96.9% (31/32), respectively. Conclusions Response to remission induction therapy can be predicted by monitoring the altered expressions of the 16 predictors in the peripheral blood at an early point of treatment in MPA patients.